STUDIES ON THE USE OF ELECTROMECHANICAL EQUIPMENT IN MINING ENTERPRISES - Maulenova Zaurexan Axmet qizi (American Journals Publishing, 2024)
This article includes research on the use of electromechanical equipment in mines, such as the mechanization of communication signals in underground mines and open pit mining. The use of such electromechanical equipment in mining enterprises is carried out based on technical conditions. The reason is that mining machines are constantly in motion in mining enterprises. Electromechanical lines and power lines in mines pose a risk. In order to prevent dangerous processes in such mining enterprises, it is necessary to install communication signals in mines based on perfect schemes.
Keywords: Mining enterprises, underground mining, electromechanical equipment in mines, communication signals.